PROM VULGAR LATIN TO SPANISH: REFLECTION ABOUT THE ORIGIN OF A ROMANCE LANGUAGE - Carrasco Tenorio, Milagros (2010)
The following anide is abour the origin of the Spanish language falls within a millenariantradition that has as a result the predecessor of Latín. In this article, we will presenta general outlook of rhis evolution on rhe basis of Vulgar Latin, without leaving asidethe classic Latin. Since rhe birth of the term Vulgar Latin, going through a historicalcontext of Romanization and a linguistic evolution of Latin that allowed the setting upof Romance languages, up ro a sumrnary of the origins of rhree Romance languages (French, Iralian and Spanish) in a written layout, will be so me of the tnain ideas of thiswork. A.., a condusion, we will presenta critica! reflection about out language ..